A novel mutation of SAR1B gene in two children with chylomicron retention disease - GEÇKİNLİ, BİLGEN BİLGE; ATA, PINAR; ARMAN, AHMET (My University, 2021)
Chylomicron retention disease (CRD) is an ultra-rare autosomal recessive syndrome with approximately 50 cases reported worldwide. CRD is characterized by malabsorption of fat, cholesterol, and fat-soluble vitamins. Biallelic mutations in the SAR1B gene encoding the SAR1BGTPase protein cause CRD. The proband is a sixteen-year-old boy who second child of healthy and consanguineous parents. His sister also had same clinical presentation. He was referred to our clinic because of having elevated creatine kinase-liver enzymes, short stature, sleep apnea, and neurodevelopmental delay. In anthropometric measurements were under the 3. Percentile. Total cholesterol, HDL, vitamin A and E levels were low, triglyceride levels were normal. Physical examination revealed low hairline, synophrisis, hypertelorism, prominent nasal root, thin upper lip, narrow and high palate, clinodactyly. In his endoscopy, distinct white mucous appearance in the second part of the duodenum was detected. Since the triglyceride level was normal and cholesterol levels were low, chylomicron retention disease was considered as a pre-diagnosis. Sanger analysis revealed a novel homozygous c.243dupA (p. Ala82Serfs*35) mutation in the SAR1B gene (NM_016103.4). Segregation analysis revealed that her parents were heterozygous, and his affected sister was homozygous. The clinical appearance of CRD begins in infancy and early childhood but may not be detected due to nonspecific symptoms. CRD should be considered in patients with growth retardation, low cholesterol value, neurological complaints, and low vitamin levels. Sleep apnea seen in proband may be a new clinical finding that had not been reported in CRD disease before. Our study reveals a novel mutation to the literature and contributes to the genotypephenotype correlation of CRD. Keywords: Chylomicron retention disease, CRD, SAR1B gene, Novel
Keywords: Chylomicron retention disease; CRD; SAR1B gene; Novel